A Scholarly Edition of Samuel P. Newman's A Practical System of Rhetoric - Hewett, Beth L., (International Studies in Human Rights ;, 2021)
In A Scholarly Edition of Samuel P. Newman's A Practical System of Rhetoric , Beth L. Hewett argues that Newman, an American nineteenth-century rhetorician, has been unfairly judged by criteria disconnected from his goals and accomplishments. His exceptionally popular textbook is important for how he engaged received theory, fit practice to the era, struggled with age-old questions of thought and language, and spoke to his readers. He operationalized the concept of taste, giving it functionality for invention, and inflected Belletrism with American illustrations suited to the nascent, uniquely American communicative requirements of a democracy. Hewett's modern scholarly edition contextualizes this book as the serious work of a scholar-educator, demonstrating its values in the context of nineteenth-century American rhetorical and textbook history.